Circulating tumor cell clusters: Insights into tumour dissemination and metastasis. (1st November 2020) - Herath, Sayuri; Razavi Bazaz, Sajad; Monkman, James; Ebrahimi Warkiani, Majid; Richard, Derek; O'Byrne, Ken; Kulasinghe, Arutha
ABSTRACT: Introduction : Metastasis results in more than 90% of cancer-related deaths globally. The process is thought to be facilitated by metastatic precursor cells, commonly termed circulating tumor cells (CTCs). CTCs can exist as single cells or cell clusters and travel through the lymphovasculature to distant organs where they can form overt metastasis. Areas covered : Studies have highlighted that CTC clusters, which may be homotypic or heterotypic in composition, have a higher metastatic potential compared to single CTCs. The characterization of CTC clusters is becoming important as heterotypic clusters can provide a mechanism for immune evasion. This review summarizes the latest advances in CTC cluster-mediated metastasis and clinical significance. Expert opinion : Comprehensive characterization of CTC clusters is needed to understand the cell types and interactions within clusters, in order to identify ways in which to reduce CTC cluster-mediated metastasis. The role of CTC clusters in prognosticating disease progression needs to be determined by documenting CTC clusters from the time of diagnosis over the course of therapy.